The Pattern of Growth and Poverty Reduction in China - Montalvo, Jose G.; Ravallion, Martin (2012)
China's rapid economic growth has been the proximate cause of the huge reduction in the incidence of poverty since 1980. Yet, the growth process has been highly uneven across sectors and regions. We test whether the pattern of China's growth mattered to poverty reduction using a new provincial panel data set constructed for this purpose. Our econometric tests support the view that the primary sector (mainly agriculture) has been the main driving force in poverty reduction. We note a number of similarities, and differences, with India.